2017
DOI: 10.4995/eurocall.2017.7014
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook to improve L2 German students’ socio-pragmatic skills

Abstract: This study explores ways of using Facebook as a tool to improve the pragmatic competence of students of German as a foreign language in Japan. Nine students of a textbook-based German class (CFER level A2) voluntarily participated in this blended learning approach, in which they were assigned weekly online tasks aimed at eliciting speech acts commonly used in online interaction. The tasks required the students write posts concerning their daily routines onto the timeline of a dedicated Facebook Group page and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…However, the study also demonstrated that the participants experienced writing challenges particularly in vocabulary and grammar. Similarly, Harting (2017) observed that preintermediate German learners in Japan mostly relied on the speech acts and expressions presented in pre-writing activities rather than incorporating the structures they encountered while engaging in authentic interactions with L2 speakers.…”
Section: Theme 1: Practicing Multiple Language Areas and Literaciesmentioning
confidence: 96%
See 4 more Smart Citations
“…However, the study also demonstrated that the participants experienced writing challenges particularly in vocabulary and grammar. Similarly, Harting (2017) observed that preintermediate German learners in Japan mostly relied on the speech acts and expressions presented in pre-writing activities rather than incorporating the structures they encountered while engaging in authentic interactions with L2 speakers.…”
Section: Theme 1: Practicing Multiple Language Areas and Literaciesmentioning
confidence: 96%
“…The universality of SNSs also meant that language learners could easily contact with native speakers (NSs) all over the world. This particular affordance of SNS was raised by a number of scholars including Jin (2015) and Harting (2017), whose research illustrated that communication with native speakers was a viable option regardless of students' geographical location. In a small case study by Hattem (2014), the evidence of negotiation of meaning was found among three Intensive Academic English Program students who practiced their grammar skills through frequent participation on Twitter.…”
Section: Theme 2: Authenticity and Negotiation Of Meaning Through Intmentioning
confidence: 99%
See 3 more Smart Citations